The Implementation Of Hibah Ruqba In Malaysia Asset Management Planning Industry In Accordance To Maqasid Shariah - Noor Lizza Mohamed Said; Mohd Zamro Muda; Zamzuri Zakaria; Adnan Mohamed Yusoff (Human Resource Management Academic Research Societ, 2024)
Vol. 12, No. 9, 2022, Page (583 – 592)